A silver–copper metallic glass electrocatalyst with high activity and stability comparable to Pt/C for zinc–air batteries. Issue 9 (10th February 2016) - Wu, Xiaoqiang; Chen, Fuyi; Zhang, Nan; Qaseem, Adnan; Johnston, Roy L.
Abstract : A silver–copper metallic glass (AgCu-MG) electrocatalyst has been fabricated for rechargeable zinc–air batteries by pulsed laser deposition. The AgCu-MG exceptionally enhances the ORR catalytic activity to a half-wave potential of 0.78 V vs. RHE after 1000 CV treatments in 0.1 M KOH. Abstract : Highly active electrocatalysts with good long term stability are vital for the commercialization of metal air batteries and alkaline fuel cells which involve the oxygen reduction reaction (ORR) at the cathode end. Herein, we developed a pulsed laser deposition (PLD) technique for the precise fabrication of silver–copper metallic glass (AgCu-MG) electrocatalysts. This PLD technique provides excellent control over the surface microtopography along with high flexibility for the deposition of different compositions of silver–copper metallic glass electrocatalysts onto nickel foam. Among all investigated Ag-based catalysts, AgCu-MG catalysts exhibit high electrocatalytic activity with a half-wave potential of 0.67 V ( vs. RHE) which can be in situ enhanced by dealloying treatment in N2 saturated 0.1 M KOH solution. In situ dealloying of the AgCu-MG provides exceptional ORR catalytic activity with a half-wave potential of 0.78 V ( vs. RHE) at 1600 rpm, which is comparable to 0.81 V ( vs. RHE) of commercial Pt/C-20%. The AgCu-MG electrocatalyst showed excellent long-term stability in rechargeable zinc–air batteries. After 1000 charge–discharge cycles at 20 mA cm −2, the discharge voltage of batteries was stable at 1.0 V demonstrating the potential application of AgCu-MG as an alternative to Pt/C-20% in zinc–air batteries and alkaline fuel cells.